1967
DOI: 10.1080/10601326708054008
|View full text |Cite
|
Sign up to set email alerts
|

Transient Changes in Topology and Energy on Extension of Polybutadiene Networks

Abstract: The theory of elasticity of polymer networks has been developed along two lines. The phenomenological approach leads to the Mooney-Rivlin relation between stress and extension ratio for uniaxial extension. The statistical theory of elasticity, based on a model for polymer molecules, predicts a similar relation with one of the constants zero. Actual elastic properties of rubbers do not agree fully with either theory.Experimental results are reported obtained with quantitatively cured polybutadiene and polyisopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1973
1973
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Considerable attention has been given by previous investigators [14][15][16][17][18][19][20][21][22][23][24][25][26] to a ratio they have denoted as I e/!, where I e is the energy component of the force and I (in contradistinction to the I used in this paper) is the total value of the force required to maintain a certain elongation at constant volume. Shen and co-workers [14,15,27] Our work yielding the value of C*/C is of course limited to very small deformations.…”
Section: Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…Considerable attention has been given by previous investigators [14][15][16][17][18][19][20][21][22][23][24][25][26] to a ratio they have denoted as I e/!, where I e is the energy component of the force and I (in contradistinction to the I used in this paper) is the total value of the force required to maintain a certain elongation at constant volume. Shen and co-workers [14,15,27] Our work yielding the value of C*/C is of course limited to very small deformations.…”
Section: Equationmentioning
confidence: 99%
“…varies with deformation. Several observers [21,23,24,26,27] had reported that I e/! at a fixed amount of cross-linking increased rapidly as the deformation approached zero, rising from values near 0.2 to 0.6 or more.…”
Section: Equationmentioning
confidence: 99%
“…The idea of entanglements acting as physical junctions was originally developed in the literature to explain deviations from the predictions for affine networks (185,213). The possibility of a contribution at equilibrium caused by trapped entanglements has been tested with model networks, ie, those prepared in such a way that the number and functionality of the cross-links are known.…”
Section: Entanglementsmentioning
confidence: 99%
“…A linear relationship was observed which represents the correlation between the filler-reinforcement effect and the amount of physical crosslinking. It has been shown that the entanglement of the rubber chains plays a considerable role in the elastic properties [42][43][44] and also in the reinforcement effect of filler in rubbery matrices. 45 This concept has been further elaborated in terms of the effect of the entanglement of chains on the mechanical properties of the rubbery materials.…”
Section: Filler-reinforcement Effectmentioning
confidence: 99%